2005 IEEE Instrumentationand Measurement Technology Conference Proceedings
DOI: 10.1109/imtc.2005.1604477
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Lift-off Effect of Phase Spectra for Eddy Current Sensors

Abstract: This paper presents an analytical model which describes the inductance change when a double air-cored coil sensor is placed next to a conducting plate. Analysis of the analytical model reveals that the phase signature of such sensor is virtually lift-off independent. This finding is verified by numerical evaluations. This paper also finds that the phase signature of a ferrite U-cored sensor can be approximated by that of a double aircored sensor of similar size, and therefore possesses similar lift-off indepen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 23 publications
0
17
0
Order By: Relevance
“…Indeed, in practice, since the sensor is placed in contact with the layered structure, the variations of the distance between the sensor and the layered structure can be assumed to be very small compared to the sensors dimensions, and hence, the lift-off effect can be neglected [15]. However, in order to simulate some variability in the sensor positioning, an additive Gaussian noise of adjustable intensity may be added to the computation results [16].…”
Section: Finite Elements Modelling Of the Problemmentioning
confidence: 99%
“…Indeed, in practice, since the sensor is placed in contact with the layered structure, the variations of the distance between the sensor and the layered structure can be assumed to be very small compared to the sensors dimensions, and hence, the lift-off effect can be neglected [15]. However, in order to simulate some variability in the sensor positioning, an additive Gaussian noise of adjustable intensity may be added to the computation results [16].…”
Section: Finite Elements Modelling Of the Problemmentioning
confidence: 99%
“…The mesurement method based on the original comprehensive model demands a large amount of computations, and hence time-consuming. The method that stems from equation (10) needs to measure the whole phase spectra [11]. Besides, it is indirect and not objective to estimate the thickness by using the comparison between the measured and precalculated phase spectra.…”
Section: Evaluation Of Plate Thicknessmentioning
confidence: 99%
“…A variety of coil designs have also been investigated. Recently, it has been reported that it is possible to significantly reduce the lift-off effect by using the phase signature abstracted from multi-frequency impedance measurement [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Non-destructive methods such as magnetic Barkhausen noise (MBN) emission [1,2] and eddy current [3][4][5] measurements have been attempted; however, no quantitative relationships between signal output and decarburisation depth have been established. Previously, we have developed electromagnetic sensors for a range of general steel measurement applications [6][7][8][9][10][11]. However, this is a specific contribution on decarburisation measurement.…”
Section: Introductionmentioning
confidence: 99%